Overcoming germination barriers through in vitro culture of mature zygotic embryos of grapevine cultivars - Costa Júnior, Otalício Damásio da; Carvalho, Virginia Silva; Generoso, Andressa Leal; Silva, Lidiane Miranda da; Sales, Roberta Aparecida de; Viana, Alexandre Pio (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2022)
Grape seeds have physical and physiological dormancy. Conventional germination methods are not very efficient. The in vitro culture of seeds and of mature zygotic embryos can be an alternative for overcoming germination barriers. The objective was to develop methodologies that increase seed germination and reduce the time to obtain seedlings. The following assays were developed: (1) conventional ex vitro germination, in a 2 × 3 factorial arrangement, of seeds with or without stratification for 90 days, from cultivars 'Niágara Rosada', 'Itália' and 'Red Globe'; (2) in vitro seed germination, in a 3 × 3 factorial arrangement, of the three cultivars and three explants (intact seeds, seeds sectioned in the micropyle region and seeds with a cross-section); and (3) in vitro germination of mature zygotic embryos, in a 4 × 2 factorial arrangement represented by four concentrations of mineral salts (MS, ½MS, WPM and ½WPM) and two cultivars ('Niágara Rosada' and 'Itália'). The conventional ex vitro germination assay resulted in a low seed germination for the three cultivars. The two types of section associated with in vitro culture provided an increase in seed germination. However, the highest germination rate (over 90%) in the shortest time (17 days) was achieved by the embryos grown in vitro. This study defines an efficient methodology to obtain high germination in grape seeds— over 85%—with uniformity and in a short time, using mature zygotic embryos grown in ½WPM culture medium. This methodology can accelerate grapevine breeding programs. Index terms: Vitis vinifera; Vitis labrusca; dormancy; seed scarification.